ANALISIS PERBANDINGAN PERENCANAAN TEBAL PERKERASAN JALAN LENTUR MENGGUNAKAN BEBERAPA METODE BINA MARGA STUDI KASUS: (RUAS JALAN PIRINGSURAT – BATAS KEDU TIMUR) - Muhammad Nauval raka Aris; Gerson Simbolon; Bagus Hario Setiadji; Supriyono Supriyono (Jurnal Karya Teknik Sipil, 2015)
Manual guidance highway pavement design issued by Directorate Jenderal Bina Marga is the result of modification to the rules of some developed countries such as AASHTO owned by United States and AUSTROADS owned by Australia. Then, the guidelines are adjusted to the condition of Indonesia to become an official guidelines that serve a reference for planning of highway pavement thickness in Indonesia.In this research, the study and the evaluation using four highway flexible pavement design guidelines starting from 2002 (Pt. T-01-2002-B) up to the latest guidance published in 2013 (No.02/M/BM/2013) with the case study Piringsurat – Batas Kedu Timur road segment. Use data as well as some of the same parameters in pavement design, in order to facilitate the conduct comparisons as traffic growth figures (i) 2,5% before 2020 and 3,5% after 2020. The result of flexible pavement thickness of four methods according to the flexible pavement design guidance, compared and assessed so as to produce an evaluation of each manual guidance flexible pavement design.